ANALISIS KONTEN SOCIAL MEDIA MARKETING TERHADAP PURCHASE INTENTION DENGAN BRAND AWARENESS SEBAGAI VARIABEL MEDIASI: SURVEI PADA FOLLOWERS INSTAGRAM @SUKABUMIFOODIES - Purwaningsih, Fitriana Ayu; Ramdan, Asep Muhamad; Norisanti, Nor (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
Digital technology is changing the way businesses compete, urging them to refine their marketing strategies. Social media has now emerged as a new phenomenon playing a crucial role in the marketing. This phenomenon is evident in the increasing number of companies and businesses utilizing social media as part of their online marketing strategies. In this study, aims to examine the influence of social media marketing on purchase intention, especially by looking at the role brand awareness as a mediating variable. The research method employed is quantitative analysis using a probability sampling technique, specifically simple random sampling. The research object is the Instagram account @sukabumifoodies, with data collected from 250 followers who responded to an online questionnaire. The data analysis technique used is Partial Least Squares Structural Equation Modelling (PLS-SEM). The results of the study indicate that social media marketing positively contributes to building brand awareness. Furthermore, brand awareness has a positive effect on purchase intention followers. In addition, brand awareness significantly mediates the relationship between social media marketing and purchase intention. These findings highlight the importance of social media marketing, brand awareness, and purchase intention in developing effective and efficient marketing strategies.